TINJAUAN TEORITIS PERSAMAAN DAN PERBEDAAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NO.16 MENURUT PERNYATAAN STANDAR AKUNTANSI KEUANGAN DAN INTERNATIONAL FINANCIAL REPORTING STANDARD. - B41108094, Nova Andra Heradian (Jurnal KIAFE, 2013)
Convergence of international accounting standards has been done by DSAK through the adoption of IFRS in full, to PSAK 16 on property, plant and equipment. This study aimed to determine whether the similarities and differences of PSAK 16 with IFRS 16, especially for fixed assets. This research was conducted with qualitative methods through comparative studies by studying and comparing the PSAK 16 and IFRS 16 to find differences and similarities. These results indicate that the differences and similarities between PSAK 16 and IFRS 16. The similarity of PSAK 16 and IFRS 16 is on the recognition and initial measurement, measurement after recognition, depreciation and derecognition. There are differences in the scope, policy changes, the transitional provisions, the effective date and the number of paragraphs. Keywords: Convergence, differences and similarities, PSAK 16 and IFRS 16.